Comparison of Discovery Learning and Problem-Based Learning Models on Concept Understanding (C1-C4) of Junior High School Students - Wahyu Sofi Martalinda (STEM Education International, 2025)
A teacher must be able to choose a learning model that has the potential to enhance students' understanding of a concept. The purpose of this research is to determine the effects of Discovery Learning (DL) and Problem-Based Learning (PBL) models on the conceptual understanding of junior high school students regarding the material on simple machines. Additionally, this study aims to compare students' understanding when taught using these two models. This quasi-experimental research employs a nonequivalent pretest-posttest control group design, involving two groups of eighth-grade students from a junior high school in Malang Regency for the 2024-2025 academic year. The sampling method used is cluster random sampling. The instruments applied in this study were multiple-choice tests. Several statistical procedures, including normality tests, homogeneity tests, independent sample t-tests, paired samples t-tests, and N-Gain tests, were utilised to analyse the data. The results indicate that both Problem-Based Learning and Discovery Learning positively affect students' conceptual understanding. However, learning through PBL resulted in a higher N-gain (%) in understanding (70.22%) than in the Discovery Learning group (55%). Based on these findings, it can be concluded that the use of DL and PBL can enhance students' understanding of concepts and encourage them to participate more actively in the learning process.